Nurses' adverse event reporting attitudes and related factors: a cross-sectional study in maternal and child specialized hospitals in China - Wu, Fang; Wang, Xin; Chen, Shaochuan; Li, Huimin; Xie, Huiqiong (Frontiers in Public Health, 2024)
ObjectiveTo investigate the current situation of nurses' attitude toward adverse event reporting and identify its related factors in maternal and child specialized hospitals.MethodsA questionnaire survey was conducted among 943 nurses in 18 second-level and above maternal and child specialized hospitals in Sichuan province in China. The questionnaire included general information and the Chinese version of Reporting of Clinical Adverse Effects Scale (C-RoCAES).ResultsThe total score of adverse events reported by nurses was 63.98 ± 8.77. The scores of the dimensions from high to low were reporting standard (3.13 ± 0.46), reporting impact (2.80 ± 0.54), reporting purpose (1.98 ± 0.66), and reporting environment (1.98 ± 0.42). Educational background (β = −1.87, p < 0.001), professional title (β = −3.51, p < 0.001), and adverse event experience (β = −7.05, p < 0.001) were the positively associated with higher levels of nurses' attitude toward adverse event reporting in maternal and child specialized hospitals (p < 0.05).ConclusionThe attitude of nurses in maternal and child specialized hospitals to report adverse events is at the middle level. Hospital managers should improve the reporting standards for adverse events, improve the hospital safety culture, strengthen the relevant training for nurses with low education and low professional titles, so as to improve nurses' awareness of adverse event reporting and reporting rate.